Comparative Study between the Laryngeal Mask Airway and Endotracheal Tube on Haemodynamic Changes for Laparoscopic Cholecystectomy Under General Anaesthesia - Hasan, Mahbubul; Rahman, Md Mushfiqur; Ekramullah, Mahmud; Shaheen, Shafiul Alam; Jabbar, Abdul; Islam, Md Rashedul (Journal of the Bangladesh Society of Anaesthesiologists, 2017)
Background: Evidence based data in the very recent years suggest that in spite of tremendous advances in contemporary anaesthetic practice and advances, airway management continue to be of paramount importance to anaesthesiologists and data regarding the outcomes of use of LMA (laryngeal mask airway) in contrast to ETT (endotracheal tube) are scanty in our clinical setup. Aims & Objectives: In this RCT (Randomized Control Clinical Trial), the ultimate aim was to depict the anaesthetic safety and haemodynamic changes of use of LMA in contrast to ETT for the patients of routine laparoscopic cholecystectomy (ASA II & III). Methods and Materials: This randomized control clinical trial (RCT) was conducted in BIRDEM General Hospital, Dhaka, Bangladesh with a total number of 60 patients (30 patients with endotracheal tube & 30 patients with LMA) were selected on the basis of systemic random sampling. The haemodynamic changes, oxygenation, ventilation and intraoperative and postoperative laryngopharyngeal complication (LPM) were noted. Results: The ultimate result of this study suggest that in Group A (ETT group), mean±SD of age was 48±1.9 and in Group B (LMA group), it was 52±1.7. Demographic status suggests that the average BMI in both group were 28.9 and 30.6 respectively. In ETT group, majority of patients (69%) had ASA grade II, in contrast, in LMA group, it was 52%. Average anaesthetic duration in both group were 45 & 50 minutes respectively. There found significant difference in haemodynamic parameter during Intubation and LMA insertion. There were no statistically significant differences in oxygen saturation (SpO2) between the two groups before or during peritoneal insufflation. Laryngeal complications, like coughing and vomiting following removal of tube were found in 6.7% and 3.3% patients respectively with the use of LMA. No case of tube leak, gastric insufflation, regurgitation, aspiration, trauma to lip, teeth, tongue, dysphagia, dysphonia and dysarthia was recorded. P-values suggests statistically insignificant result here (>0.05). Conclusion: The effectiveness and safety of LMA in terms of intra and postoperative haemodynamic status, SaO2 and laryngeal complications are clinically comparable to those of endotracheal tube. And LMA insertion causes less changes of haemodynamic parameters when compared with that of ET intubation. Our finding suggests that LMA can be safe and beneficial alternative to ETT. JBSA 2017; 30(1): 34-40